2012
DOI: 10.2174/156652412800619978
|View full text |Cite
|
Sign up to set email alerts
|

GADD45 Proteins: Central Players in Tumorigenesis

Abstract: The Growth Arrest and DNA Damage-inducible 45 (GADD45) proteins have been implicated in regulation of many cellular functions including DNA repair, cell cycle control, senescence and genotoxic stress. However, the pro-apoptotic activities have also positioned GADD45 as an essential player in oncogenesis. Emerging functional evidence implies that GADD45 proteins serve as tumor suppressors in response to diverse stimuli, connecting multiple cell signaling modules. Defects in the GADD45 pathway can be related to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
211
0
5

Year Published

2014
2014
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 273 publications
(228 citation statements)
references
References 171 publications
(203 reference statements)
12
211
0
5
Order By: Relevance
“…26,27 The increased expression of these two antiproliferation FoxO targets could also contribute to antineoplastic and antigenotoxic effects of cGMP signaling, which have been reported previously. 21,53,54 FoxO3a could therefore serve many functions in the differentiated colon epithelium, but we demonstrated herein that it can protect these cells from oxidative stress, as has been described recently for quiescent cells. 33 FoxO expression at the luminal border would therefore augment epithelial barrier resiliance to the destructive effects of ROS that are known to be generated by commensal bacteria.…”
Section: Pkg2 Activates Foxo3a In the Colonsupporting
confidence: 75%
“…26,27 The increased expression of these two antiproliferation FoxO targets could also contribute to antineoplastic and antigenotoxic effects of cGMP signaling, which have been reported previously. 21,53,54 FoxO3a could therefore serve many functions in the differentiated colon epithelium, but we demonstrated herein that it can protect these cells from oxidative stress, as has been described recently for quiescent cells. 33 FoxO expression at the luminal border would therefore augment epithelial barrier resiliance to the destructive effects of ROS that are known to be generated by commensal bacteria.…”
Section: Pkg2 Activates Foxo3a In the Colonsupporting
confidence: 75%
“…Functions of GADD45 family proteins are similar, but not identical, and their induction differs under diverse physiological conditions or in different cell types. 43 GADD45A, one of the most critical downstream targets of tumor suppressor TP53 and BRCA1, 44 45,46 Hence, these findings prompted us to study whether GADD45A can induce an autophagy response and what is the underlying mechanism. In this study, through western blot and immunofluorescence assays for specific markers of the autophagic system, we found that the number of autophagosomes in GADD45A knockout mice and MEF cells significantly increased as a result of GADD45A deletion.…”
Section: Gadd45gmentioning
confidence: 99%
“…GADD45 is one of the growth arrest and DNA-damage-inducible genes (GADD) that plays a pivotal role in cellular genotoxic and nongenotoxic stress responses, acting as stress sensor and tumor suppressors. 41 Studies have shown that cells exhibit uncontrolled proliferation when GADD45 is repressed. 42 Altogether, the results presented here show that TiO 2 nanofibrous surface structures could account for their morphogenic effect in triggering cell proliferation and regulating normal cell cycle progression.…”
mentioning
confidence: 99%